Why Variation Theory Marks an Important Stage in the Study of Comparative Literature - Li Haiying; Theo D’haen (Comparative Literature: East & West)
Since its official proposal in 2005, Variation Theory has received significant attention and high praise from academic circles both domestically and abroad. Theo D’haen, editor-in-chief of The European Review, and Professor of English Comparative Literature at the University of Leuven in Belgium, also spoke highly of it. Theo D’haen said, “Professor Cao Shunqing’s Variation Theory of Comparative Literature marks a constitutive phase in Chinese comparative literature’s relationship to the discipline of comparative literature in general.” Therefore, the author interviewed Professor Theo D’haen on the topic of “Why Variation Theory Marks an Important Stage in the Study of Comparative Literature.” In Theo D’haen’s view, “Cao’s variation theory contributes to the greater acceptance of translated literature….it also fosters worldwide cultural and literary dialogue. “Cao’s variation theory is an original and important contribution to international comparative literature studies and a decisive step on the road to a specifically Chinese variant of comparative literature studies.”